KEPEMIMPINAN PARTISIPATIF KEPALA SEKOLAH DALAM PENGELOLAAN PENDIDIK DAN TENAGA KEPENDIDIKAN DI SMPIT AL-MUMTAZ - Asmawarni, Asmawarni; Radiana, Usman; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of the study was to describe the participatory leadership of school principals in the management of educators and education personnel at SMPIT Al-Mumtaz Pontianak. The form of case study research is a qualitative approach. Methods of data collection by interview, document and observation. Miles and Huberman's interactive data analysis model is by condensing data, presenting data and drawing conclusions. Test the validity of the data using the credibility test, namely the extension of the observation period, increasing persistence and triangulation.The main findings of the study (1) The decision-making process is carried out jointly through the mechanism of regular meetings, tiered in each section. (2) The Foundation holds the highest authority the leadership is collegial in nature. The principal distributes part of his power to educators and education staff as deputy principals in charge of curriculum, student affairs, infrastructure and treasurer and administration. (3). The principal empowers educators and education staff by providing additional tasks beyond the main task (4) The principal controls educators and education staff with Islamic personal development programs, academic supervision, monthly evaluation meetings and approaches.